2009
DOI: 10.1096/fj.09-138347
|View full text |Cite
|
Sign up to set email alerts
|

Androgen action via testicular peritubular myoid cells is essential for male fertility

Abstract: Androgens are essential for normal spermatogenesis and male fertility, but how androgens exert this effect remains uncertain. Androgen receptors (ARs) are expressed in several testicular cell types, but continuing uncertainty exists over which cell type mediates androgen control of spermatogenesis. Androgen signaling via Sertoli cells (SCs) is essential for complete spermatogenesis, but the role for androgen signaling via peritubular myoid (PTM) cells is contentious. To address this controversy, we generated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
215
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 215 publications
(231 citation statements)
references
References 46 publications
11
215
1
4
Order By: Relevance
“…S1). The Myh11-cre was effective at disrupting the Ar gene in PM cells (23). We confirmed that MYH11 is present in PM cells by immunostaining (Fig.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…S1). The Myh11-cre was effective at disrupting the Ar gene in PM cells (23). We confirmed that MYH11 is present in PM cells by immunostaining (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Previous studies demonstrated that (i) cKO of the Ar gene in PM cells resulted in infertility (23), (ii) androgen response elements (AREs) were present in the promoter region of the Gdnf gene in mice (67), (iii) GDNF was essential for SSC maintenance in vitro (1,9,26), and (iv) PM cells isolated from human testes produced GDNF (68). We recently reported that (i) PM cells in adult mice produce GDNF, (ii) isolated PM cells from adult mice produce GDNF in response to T treatment, and (iii) SSCs co-cultured with T-treated PM cells are significantly more effective at repopulating the testes of germ cell-depleted mice following transplantation than SSCs co-cultured with untreated PM cells (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no means of specifically targeting KO of Ar in the adult Leydig stem cells, because the only presently known markers are COUP-TFII and AR, both of which are also expressed in peritubular myoid cells, and KO of Ar in the latter has phenotypic consequences, including on adult Leydig cells (38,39). We, therefore, investigated development of adult Leydig stem cells in complete ArKO mice.…”
Section: Resultsmentioning
confidence: 99%
“…Male congenic C57BL/6J mice hemizygous for an aP2-Cre transgene (37) were mated to homozygous R26R-EYFP females (73). The +/aP2-Cre:+/R26R-EYFP and +/+ :+/R26R-EYFP (control) male offspring from these matings were genotyped as previously described (38).…”
Section: -Hsd3mentioning
confidence: 99%